2013
DOI: 10.1111/jcal.12017
|View full text |Cite
|
Sign up to set email alerts
|

Persistence temperament associated with children playing math games between touch panel and embodied interaction

Abstract: The different designs of various interactive gaming controllers affect posture and muscle loading of the body. It is assumed that prolonged exposure to the interactive gaming controllers can affect the effectiveness in using the game for the purposes of learning. This study explores the differences in behavioural responses among students with different temperaments regarding mathematic gameplay by comparing the touch-based and gesturebased interactive devices. The experiment was designed for 119 5-year-old kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Structural attributes are non-content presentation features, including feedback and scaffolding (e.g., "Solution" scaffold revealing a worked example). Further evidence of personal attributes of subjects [46,47] and structural attributes of artifacts [38,48,49] is present in other literature.…”
Section: Attributesmentioning
confidence: 78%
“…Structural attributes are non-content presentation features, including feedback and scaffolding (e.g., "Solution" scaffold revealing a worked example). Further evidence of personal attributes of subjects [46,47] and structural attributes of artifacts [38,48,49] is present in other literature.…”
Section: Attributesmentioning
confidence: 78%
“…al., 2012). Not only in the education of mathematics but also in language (Jong, Hong & Yen, 2013), science (Clark, Nelson, Sengupta & D'Angelo, 2009), engineering and positive sciences (Mayo, 2007), health and medical sciences (Boulos, Hetherington & Wheeler, 2007), physical education (Papastergiou, 2009) and many more fields, digital games contribute to the teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, TBI was more favoured over GBI for kindergarten children. Jong et al (2013) added that more emphasis on TBI would be a great move for e-learning designers.…”
Section: Temperament Based Learningmentioning
confidence: 99%
“…She concluded that "acknowledging temperament-based guidance would show that each child has a particular behavioural style that contributes to his or her development and to the social environment". Jong et al (2013) stated that the posture and muscle loading of the body is significantly affected by various different interactive gaming controllers. It has been argued that the period of exposure to the interactive gaming controllers affects the success in using the game for the purposes of learning.…”
Section: Temperament Based Learningmentioning
confidence: 99%
See 1 more Smart Citation